A ball microscope for viewing the entire surface of amphibian embryos. (October 2021) - Crawford-Young, Susan J.; Young Williment, Janet L.
Abstract: Waves on the surface of developing eggs/embryos need to be viewed from all sides of their 3D tissue. The ball microscope will enable tracking of cellular waves and determine their interactions with the cells on the surface. Nine microscopes are arrayed in a spherical formation around an imaging stage to create whole surface images of objects anywhere from 0.5 mm 3 to 60 mm 3 in size. The 3D printed ball-based microscope is made using nine, Opti-Tekscope OT-HD Digital USB Microscope Camera Magnifiers. Eight of the microscope cameras fit into the ball at 90° angles to each other and one bottom microscope is used for a base to hold the stage. The base will support a customised cuvette to hold the embryo in water. The microscopes are the size of a pen (13 cm long and 1 cm in diameter) and each have a ring light around their diameter for self illumination. The nine microscopes can be attached to a microcontroller for time-lapse automated imaging. This microscope will be compared to other microscopes developed for the same purpose. The microscope can be used for time lapse imaging of the surface of small 3D objects and can be used to view Axolotl salamander embryo development as the Axolotl embryos are 2 mm in diameter. Other amphibian eggs can also be imaged using this technique.